Omics-based insights into skin ulcerative disease in sea cucumbers: a systematic review - Deepak Ganesh; Vijay Subbiah Kumar; Guneswar Sethi; Nurzafirah Mazlan (Molecular Biology Reports, 2026)

A step-by-step approach to establishing an efficient genetic transformation protocol for Chlorella vulgaris using electroporation - Dexter Miller Robben; Zarina Amin; Cahyo Budiman; Vijay Subbiah Kumar (Molecular Biology Reports, 2026)

Evaluation of Immune Gene Expression Reveals Immunomodulatory Activity of Chlorella vulgaris in a Mouse Model - Dexter Miller Robben; Zarina Amin; Cahyo Budiman; Vijay Subbiah Kumar (Biochemical Genetics, 2026)

In Silico Identification of MYB Transcription Factors Involved in Mangosteen Anthocyanin and Xanthone Production - Ching-Ching Wee; Masanori Arita; Intan Azlinda Ramlee; Nor Azlan Nor Muhammad; Vijay Kumar Subbiah; Hoe-Han Goh (Tropical Plant Biology, 2026)

The effect of chronic microplastic exposure on the growth, biochemical responses, and histological changes of the juvenile sea cucumber Holothuria scabra - Sarah Syazwani Shukhairi; Nurzafirah Mazlan; Nur Nashrah Abd Rahman; Muhammad Nor Afdall Nazahuddin; Amir Syazwan Shawel; Vijay Subbiah Kumar (Environmental Science and Pollution Research, 2025)
Microplastics (MPs) are minuscule plastic particles less than 5 mm in size, originating from the degradation of larger plastic debris. MPs originate from various sources and pose a significant threat to the marine ecosystem. Holothuria scabra is a species of sea cucumber with high commercial value and among the organisms affected by MPs pollution. H. scabra are also crucial in maintaining a clean seabed and recycling nutrients in the ocean ecosystem. Polymethymethacrylate (PMMA), a durable and transparent plastic polymer widely used as a glass alternative in maritime and other industries. This research aimed to investigate the toxicity effects of polymethylmethacrylate-MPs on the well-being of juvenile sea cucumber H. scabra . Over a 60-day treatment period, polymethylmethacrylate MPs were exposed to the juvenile sea cucumber diet at concentrations of 0.6 MPs/g (Treatment 1), 1.2 MPs/g (Treatment 2), and 10 MPs/g (Treatment 3) while a control group which received no MPs exposure to observe changes in their growth, biochemical responses, and histological alteration. The mean weight, weight gain percentage and specific growth rate exhibited significant differences ( p < 0.05) with the control group displaying the highest SGR value of 1.22 ± 0.35%. Mortality was observed in treatment 2 and 3, respectively. A disruption in enzyme activity was also observed across all treatment groups ( p < 0.05). The findings of growth rates and biochemical responses were further supported by histological observation, uncovering injuries and loss of cellular components in respiratory trees and intestines. This study enhances our understanding of the toxicity mechanism associated with PMMA-MPs in deposit feeder organisms.

Evaluation of Microplastics Ingested by Sea Cucumber Holothuria Scabra from Pulau Jambongan, Sabah - Sarah Syazwani Shukhairi; Nurzafirah Mazlan; Vijay Kumar Subbiah; Nur Nashrah Abd Rahman; Muhammad Nor Afdall Nazahuddin; Amir Syazwan Shawel; Audrey Daning Tuzan; Sitti Raehanah Muhammad Shaleh; Norfazreena Mohd Faudzi; Rossita Shapawi; Muhammad Dawood Shah; Tze Young Thung (Bulletin of Environmental Contamination and Toxicology, 2025)

Genomic structure of the native inhabitants of Peninsular Malaysia and North Borneo suggests complex human population history in Southeast Asia - Chee-Wei Yew; Dongsheng Lu; Lian Deng; Lai-Ping Wong; Rick Twee-Hee Ong; Yan Lu; Xiaoji Wang; Yushimah Yunus; Farhang Aghakhanian; Siti Shuhada Mokhtar; Mohammad Zahirul Hoque; Christopher Lok-Yung Voo; et al. (Human Genetics, 2018)